The Centre Holds : Report from the Dutch art scene. - Fuchs, Rudi H. (Köln : Galerie Gmurzynska, 1998)
Aalders, Steven ; Ayres, Tim ; Bade, David ; Birza, Rob ; Dumas, Marlene ; Hermans, Renoît ; Jacklin, Michael ; Koelewijn, Job ; Lamers, Kiki ; van Lieshout, Erik ; Atelier van Lieshout ; Mik, Aernout ; Preesman, Avery ; Schnitger, Lara ; Schouten, Marien ; Schuil, Han ; Theuws, Roos ; Zandvliet, Robert
biografie
The Centre Holds : Report from the Dutch art scene, Galerie Gmurzynska, Köln, 9 November 1998 - 30 January 1999
Engels
boek